Krankzinnigenzorg in België (1850-1900): Collocatie en Dwang - Hermans, Goedele (Studium, 2013)
Mental health care in Belgium (1850–1900): compulsory admission and coercionAfter the declaration of the Lunacy law of June 18th, 1850, the Belgian government became increasingly involved in the organization of psychiatric care. Doctors were given a huge responsibility by making compulsory admission a medical procedure. The position of the so-called aliéné was ultimately the result of negotiations between the madman himself, his family, doctors and the government. To understand how coercion was inscribed in a reformatory movement that claimed a more humane and scientific approach to insanity I researched the various influences that were at play. Sources from the établissement des aliénés de Frères Alexiens de Louvain were used to study the position of the aliéné in the second half of the nineteenth century. The compulsory admission forms and the data on the use of coercive tactics shed light on the hopeful reformation and its decline caused by low cure rates and a growing overpopulation of asylums. The relation between the government and the alienists was characterized by a complex balance between freedom and control. Families and doctors also had a relationship that was complicated because of mutual distrust. The position of the aliéné grows more complicated when we look at these influences. Most of the time, the mental patient was doomed to undergo the decisions made for him by his family, his doctor or the government. However, as specialized treatment, scientific study and government policy grew, the mental patient also became someone who would no longer be ignored.